2010
DOI: 10.1016/j.bbr.2010.05.052
|View full text |Cite
|
Sign up to set email alerts
|

The role of sleep and practice in implicit and explicit motor learning

Abstract: Sleep is hypothesized to play a functional role in the consolidation of memory, with more robust findings for implicit, than explicit memory. Previous studies have observed improvements on an explicit motor task after a sleep period. We examined the role of massed practice and sleep on implicit and explicit learning within a motor task. Controlling for non-sleep factors (e.g. massed practice, circadian confounds) eliminated both explicit and implicit learning effects that have been attributed to sleep. Keyword… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…Indeed, texture discrimination training and testing sessions entail more than 1000 trials, and performance has been shown to deteriorate if participants are retested multiple times during the day, implicating fatigue in the visual system as a critical factor in the reported pattern of performance changes (Mednick et al, 2002). Additionally, similar inhibition effects were recently discovered for motor pursuit learning (Rieth et al, in press), suggesting that confounding inhibition effects may be common in procedural tasks. Collectively, these studies further challenge the procedural memory consolidation model defined by a time-dependent stabilization and a sleep-dependent enhancement phase.…”
Section: Discussionsupporting
confidence: 63%
“…Indeed, texture discrimination training and testing sessions entail more than 1000 trials, and performance has been shown to deteriorate if participants are retested multiple times during the day, implicating fatigue in the visual system as a critical factor in the reported pattern of performance changes (Mednick et al, 2002). Additionally, similar inhibition effects were recently discovered for motor pursuit learning (Rieth et al, in press), suggesting that confounding inhibition effects may be common in procedural tasks. Collectively, these studies further challenge the procedural memory consolidation model defined by a time-dependent stabilization and a sleep-dependent enhancement phase.…”
Section: Discussionsupporting
confidence: 63%
“…Error bars represent ±1 SEM. Asterisks represent significance at P < 0.05. opportunistic manner (40), such as in times of low external input (i.e., during a quiet wake period or during sleep), as has been shown in auditory tone sequence learning (41), visual search (42), and pursuit motor tasks (43). In contrast, some nondeclarative information, such as our Primed condition here, mainly rely on sleep processes (5,44,45).…”
Section: Resultsmentioning
confidence: 64%
“…Similar improvements in procedural memory over sleep have been observed for a number of other tasks, e.g., visual texture discrimination, finger sequence tapping, or mirror tracing. It has been suggested that sleep enhances performance either by actively supporting consolidation of memory traces associated with the task or by removing training-related fatigue [34][37]. Second, there was an additional advantage for repeated over non-repeated target-distractor configurations, which was also larger in the nap than rest group.…”
Section: Discussionmentioning
confidence: 99%